2014
DOI: 10.1068/a130071p
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging Life: Appreciations of a Secondhand ‘Capital’ Machine

Abstract: Abstract:In this paper I look at a farm that diversified its business and within this process bought a second-hand sausage vacuum-filler. I do this in order to question how this machine came to be understood and valued by the farmers who bought it. The themes discussed include the role of the machine in changing the working practices of the farm, as well as factors unknown when buying second-hand -purchasers can only ever truly know the reliability and levels of performance of the machine retrospectively. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…We further found that four studies used secondhand consumption in the area of luxury items purchasing (Keim & Wagner, 2018; Kessous & Valette‐Florence, 2019; Turunen et al, 2020; Turunen & Leipämaa‐Leskinen, 2015a) as the independent variable. Similarly, six studies used the constructs reinforced by secondhand consumption in the context of sustainable consumption as the independent variable (Aida & Terazono, 2010; Hischier & Böni, 2021; Lee & DeLong, 2021; Norris, 2015; Spiller, 2014; Turunen & Pöyry, 2019). While these studies have laid the groundwork for comprehending the impact of secondhand consumption, further investigation is necessary to gain a deeper understanding of consumer motives for engaging in secondhand consumption.…”
Section: Way Forward: a Research Agenda For Secondhand Consumption Ba...mentioning
confidence: 99%
“…We further found that four studies used secondhand consumption in the area of luxury items purchasing (Keim & Wagner, 2018; Kessous & Valette‐Florence, 2019; Turunen et al, 2020; Turunen & Leipämaa‐Leskinen, 2015a) as the independent variable. Similarly, six studies used the constructs reinforced by secondhand consumption in the context of sustainable consumption as the independent variable (Aida & Terazono, 2010; Hischier & Böni, 2021; Lee & DeLong, 2021; Norris, 2015; Spiller, 2014; Turunen & Pöyry, 2019). While these studies have laid the groundwork for comprehending the impact of secondhand consumption, further investigation is necessary to gain a deeper understanding of consumer motives for engaging in secondhand consumption.…”
Section: Way Forward: a Research Agenda For Secondhand Consumption Ba...mentioning
confidence: 99%
“…We define farm diversification in terms of 'livelihood' (Hussein and Nelson, 1998). This includes on-and-off-farm activities, resources and skills, which generate extra income by creating additional agricultural or non-agricultural products, or supplement farm incomes by selfemployment or paid labour (Spiller, 2015). Diversification relates to strategically systematic planned movement away from core business activities (McElwee, 2006).…”
Section: Introductionmentioning
confidence: 99%